2015
DOI: 10.1007/s12663-015-0770-9
|View full text |Cite
|
Sign up to set email alerts
|

Superolateral Dislocation of the Mandibular Condyle: A Series of Seven Cases

Abstract: Introduction Anterior and anteromedial dislocations of the mandibular condyle are seen frequently in mandibular fractures. Less frequent are dislocations of the condylar head in the lateral, medial and posterior direction whereas superior dislocation into the middle cranial fossa is rare. We report a series of seven cases encountered over the years, which, incidentally, is the largest case series reported till date with lateral and superolateral dislocation of the condyle after a traumatic injury. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Contrary to this, some reports suggest that superolateral dislocations can take place without any associated mandibular fracture . According to Li et al , for such dislocation to occur, the prerequisite factors are multiple multidirectional impacts of force, wide open mouth and flabby joint capsule and pterygoid muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to this, some reports suggest that superolateral dislocations can take place without any associated mandibular fracture . According to Li et al , for such dislocation to occur, the prerequisite factors are multiple multidirectional impacts of force, wide open mouth and flabby joint capsule and pterygoid muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Closed reduction methods are successful in cases in which early diagnosis of the injury has been made. Studies have shown good results with closed reduction of superolateral dislocation of mandibular condyle . Delay in the reduction may make closed reduction impossible because of the development of fibrosis within the joint cavities, myospasm, bony union or a combination of these .…”
Section: Discussionmentioning
confidence: 99%
“…The rest 6 cases were type I dislocated. The Worthington described his type of case with the term unusual and the information was not available for the case of Radhakrishkna (Table III) (Table IV) [1][2][3][4]7,10,12,13,[22][23][24][25][26][27][28] while 34 dislocations (46.26%) was managed by surgical modalities [5][6][7]9,11,14,[16][17][18][19][20][21][22]24,26,27,29] while no treatment was given for 2 cases (2.98%) resulting in fibrosseous ankylosis [4] (Table V). It can be concluded that most of all surgeons had used open reduction techniques for management of supero-lateral dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Kotak rajkumar et al [27] did capsulorraphy by suturing split thickness temporalis myofascial flap on lateral aspect of capsule was to prevent repeated early dislocation of superolateral condyle. The closed reduction/non surgical technique mostly had been managed by manual manipulation under sedation [2] or general anesthesia [3,26] with muscle relaxants. Worthington [1] had tried managing his case by passing a wire through bone at left angle to facilitate downward traction but no avail and finally open reduction was done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation